A CURE FOR RECENTLY ACQUIRED HEPATITIS C - Radka Komitova; Georgi Kiprin; Elica Golgocheva-Markova (Peytchinski Publishing, 2022)
Chronic hepatitis C is a global health threat. Most individuals infected with the hepatitis C virus (HCV) will inevitably progress to chronic infection, leading to cirrhosis and hepatocellular carcinoma. The current use of direct-acting antiviral (DAA) agents has changed the outlook for the treatment resulting in a cure for a short time. Recently acquired hepatitis C, also known as acute hepatitis, should be treated with regimens similar to chronic hepatitis C. We report a case of recently acquired hepatitis C manifested with jaundice, confirmed by a positive HCV RNA result and seroconversion. The patient was referred to a gastroenterologist with his girlfriend with newly diagnosed chronic hepatitis C for further evaluation and treatment. Both underwent DAA treatment with glecaprevir/pibrentasvir for two months. Upon completion of the therapy and 12 weeks later, HCV PCR was undetected in both cases. We treated our patient long before the onset of chronic liver disease and long-term complications. The current case underscores the importance of asking about potential ongoing exposure to an HCV-infected person.